2014
DOI: 10.1016/j.lfs.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial transplantation of human umbilical cord blood mononuclear cells in neonatal hypoxic–ischemic rats

Abstract: Our findings contribute to the translational knowledge of cell based-therapy in neonatal HI and demonstrate for the first time that IA transplantation into rat pups is a feasible route for cellular delivery and prevents long-term cognitive deficits induced by experimental neonatal HI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The large variation in infarct size makes the small morphological changes undetectable. Several studies on neonatal HIE have reported the beneficial effects of cell therapies in behavioral tests without any morphological improvement [11,36,37]. Such reports show that the lack of morphological improvement does not preclude an improvement in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The large variation in infarct size makes the small morphological changes undetectable. Several studies on neonatal HIE have reported the beneficial effects of cell therapies in behavioral tests without any morphological improvement [11,36,37]. Such reports show that the lack of morphological improvement does not preclude an improvement in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the report of intra-arterial transplantation [10], the transplant did not restore stereological volume in the damaged tissue even though long-term adverse cognitive effects were reduced. This would suggest that there were positive influences of the transplant on remaining intrinsic cells, but not cell replacement.…”
Section: Summary Of Acute Preclinical Studiesmentioning
confidence: 97%
“…Some studies demonstrate that a higher dose is more beneficial [14,38,39], while a study does not confirm it [67].…”
Section: Cell Typementioning
confidence: 99%